Students' perceptions of learning, using interactive notes - Papageorgiou, E. (South African Journal of Higher Education, 2021)
Orientation: The main purpose of teaching should be to encourage and promote learning. Purpose: To assist lecturers to gain additional information about how students learn, through the use of “interactive notes”, as opposed to “comprehensive notes” that could affect their academic performance. Due to the lack of student engagement in large classes, the study investigated students’ perceptions of learning in lectures to establish how students learn and whether they have learnt and/or acquired knowledge in lectures. Research Problem: The research question was “what teaching aids/tools accounting students prefer in relation to their race, gender, language and/or academic performance on how students learn and/or acquire knowledge in lectures”? Methodological approach: The research study was exploratory; N=382 students participated in the study at a South African university. Standard multiple regression analysis was employed and statistical tests were conducted to determine the relationships between categorical variables to answer the research question. Major findings: The findings provide a source for educators to introduce interactive learning in lectures. An increase in students’ academic performance was noted with the inclusion of “interactive notes” in lectures. We also find that students learn better when they actively engage, participate and interact in lectures when taking notes. Conclusion: The value of the study contributes to the knowledge of research in addressing first-year students’ learning perceptions in a more effective learning environment.